An introduction to syntax - Valin, Robert D Van (Cambridge University Press, 2013)
Clearly organized and accessible, this comprehensive textbook provides students with a thorough grounding in the analysis of syntactic structure using data from a typologically wide variety of languages. It includes a chapter on theories of syntax and each chapter includes generous exercises and recommendations for further study.